2020
DOI: 10.1097/prs.0000000000007028
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Breast Implant Irrigant Solutions: A Comparative Analysis Using an In Vitro Model

Abstract: Background: Infections are challenging complications of implant-based breast reconstruction and augmentation. They pose a clinical challenge, with significant economic implications. One proposed solution is implant irrigation at the time of placement. There is no consensus on the optimal irrigant solution. Methods: The authors tested the relative efficacy of 10% povidone-iodine, Clorpactin, Prontosan, triple-antibiotic solution, or normal saline (negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 49 publications
1
43
0
Order By: Relevance
“…epidermidis shows 1 log reduction after 30 minutes of exposure. 50 Combined, these results suggest that a much longer exposure time may be required to significantly reduce biofilm-associated bacteria compared with planktonic bacteria. Given the varying clinical utilization patterns and protocols, TAB effectiveness may vary greatly, depending on the amount of residual antibiotic solution that may persist in the pocket.…”
Section: Discussionmentioning
confidence: 91%
“…epidermidis shows 1 log reduction after 30 minutes of exposure. 50 Combined, these results suggest that a much longer exposure time may be required to significantly reduce biofilm-associated bacteria compared with planktonic bacteria. Given the varying clinical utilization patterns and protocols, TAB effectiveness may vary greatly, depending on the amount of residual antibiotic solution that may persist in the pocket.…”
Section: Discussionmentioning
confidence: 91%
“…This study also investigated defined endpoints for exposure to antimicrobial solutions with the active agent neutralized from further activity at these timepoints; therefore, the results do not preclude that TAB may be more efficacious when left in the breast pocket for longer contact times as has been suggested by other studies. 22 , 38 Furthermore, the assay setup in this study is a simplified 2-dimensional in vitro testing platform, which did not utilize surrogate silicone surfaces in lieu of breast implant materials; however, a recently published study utilized smooth silicone coupons and demonstrated very similar results regarding PI and TAB efficacy against S . aureus and S .…”
Section: Discussionmentioning
confidence: 99%
“…epidermidis , lending credence to the applicability of our results to silicone surfaces. 38 Given these limitations, the correlation between the results of these in vitro studies and clinical outcomes is not known and could be further investigated through appropriate in vivo preclinical studies and clinical work. However, these in vitro findings are supported by the outcomes reported for utilizing PI in pocket irrigation in recent clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…While in cosmetic breast augmentation its incidence is around 0.1–1.5%, it rises to 5.8–28% in breast reconstruction, depending on the study ( ISAPS, 2019 ). Consequences of these infections are a delay in starting adjuvant chemotherapy or radiotherapy treatment and additional surgeries with a significant increase in the risk of reconstructive failure and/or implant loss ( Ranganathan et al, 2018 ; Ngaage et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…As for BI colonizing microorganisms, the most frequently isolated in implant culture is Staphylococci ( S. epidermidis and S. aureus ) and anaerobes, which are associated with treatment-resistant infection and implant loss ( Del Pozo et al, 2009 ; Deva et al, 2013 ; Rieger et al, 2013 ; del Pozo and Auba, 2015 ; Ngaage et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%